2019
DOI: 10.1016/s2468-1253(19)30347-4
|View full text |Cite|
|
Sign up to set email alerts
|

The global, regional, and national burden of pancreatic cancer and its attributable risk factors in 195 countries and territories, 1990–2017: a systematic analysis for the Global Burden of Disease Study 2017

Abstract: Background Worldwide, both the incidence and death rates of pancreatic cancer are increasing. Evaluation of pancreatic cancer burden and its global, regional, and national patterns is crucial to policy making and better resource allocation for controlling pancreatic cancer risk factors, developing early detection methods, and providing faster and more effective treatments. Methods Vital registration, vital registration sample, and cancer registry data were used to generate mortality, incidence, and disability-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
246
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 447 publications
(259 citation statements)
references
References 39 publications
4
246
1
8
Order By: Relevance
“…The present study showed that most UC patients were diagnosed at the age of 60-70 years, with a slight male predominance. These clinical features were similar to those of PC [2] [23] [24]. It has been reported that UC of the pancreas expressed epithelial-mesenchymal transition (EMT) markers (e.g.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The present study showed that most UC patients were diagnosed at the age of 60-70 years, with a slight male predominance. These clinical features were similar to those of PC [2] [23] [24]. It has been reported that UC of the pancreas expressed epithelial-mesenchymal transition (EMT) markers (e.g.…”
Section: Discussionsupporting
confidence: 70%
“…It has been estimated that, in 2020, approximately 47,050 patients will die of this disease [1]. Global data showed that 448,000 patients were diagnosed with PC in 2017, with a 2.3-times increase in the number of incident cases and deaths from 1990 to 2017 [2]. Despite efforts to develop new treatments [3] [4], the prognosis of PC patients remains poor, and the morbidity is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…PDAC represents the fourth most common cause of cancer death in the Western world, with an estimated incidence of more than 40,000 cases per year in the United States and 448,000 cases globally. It is one of the most devastating, aggressive and lethal tumors, characterized by a 5-year survival for all stages of the disease <7% [2][3][4], due to the high incidence of recurrence and metastases dissemination [5].…”
Section: Introductionmentioning
confidence: 99%
“…The age-standardized incidence rate of pancreatic cancer increased by 1.03% per year from 1973 to 2014 [6]. Changes in environmental and behavioral factors rather than genetic factors are thought to be related to the worldwide increase in pancreatic cancer [7].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence is signi cantly different among geographical areas; the highest incidence is found in Europe and North America, while the lowest is found in Africa and South Central Asia [8]. Differences in lifestyle (e.g., high-calorie diet and high body mass index), exposure to environmental risk factors (e.g., smoking), and accessibility to medical services including more e cient diagnostic tools might be associated with the variability in the mortality of pancreatic cancer among countries [7,9,10]. A recent study showed that pancreatic cancer is ranked as the 14th most common cancer and the 7th most common cause of cancer mortality worldwide [8]; however, the socioeconomic burden of pancreatic cancer is expected to increase globally in the near future.…”
Section: Introductionmentioning
confidence: 99%